2015
DOI: 10.1038/srep16468
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effects of FTY720 Ophthalmic Solution on Corneal Allograft Survival

Abstract: Fingolimod (FTY720), a novel class of sphingosine 1-phosphate receptor modulators, has received special interest among ophthalmologists, particularly given that oral administration of FTY720 has proven to effectively treat corneal graft rejection in animal models. However, no studies have examined the performance of FTY720 as an ophthalmic solution in reducing corneal rejection in high-risk corneal rejection models, and the stability and ocular irritation profile of FTY720 ophthalmic solution are also unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Therefore, ani-rejection therapy after keratoplasty is of paramount importance for preserving the vision of patients, especially in high-risk cases. However, due to their low solubility, unfavorable stability, or side effects, traditional immunosuppressants are unsatisfactory for clinical application ( 33 ). Although emerging evidence had demonstrated that RAPA was a novel immunosuppressive agent for prevention of corneal-allograft rejection ( 15 19 ), its water insolubility and the existence of a blood/eye barrier has restricted its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ani-rejection therapy after keratoplasty is of paramount importance for preserving the vision of patients, especially in high-risk cases. However, due to their low solubility, unfavorable stability, or side effects, traditional immunosuppressants are unsatisfactory for clinical application ( 33 ). Although emerging evidence had demonstrated that RAPA was a novel immunosuppressive agent for prevention of corneal-allograft rejection ( 15 19 ), its water insolubility and the existence of a blood/eye barrier has restricted its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In the rat penetrating keratoplasty model, retaining the interrupted sutures and exposing suture nodes to induce corneal neovascularization may lead to a high probability of graft rejection. [38][39][40][41] Accordingly, this animal model possesses, to some extent, the characteristics of a high-risk transplant. Therefore, the sutures were not removed in some studies; in contrast, graft sutures were removed in other studies to mimic penetrating keratoplasty in patients.…”
Section: Discussionmentioning
confidence: 99%
“…a Albino rabbit eye following application of the standardized Draize test, a common toxicity assay using clinical scoring post-topical irritant application to appropriately label chemicals based on their propensity to cause corneal damage (Wilhelmus, 2001). Image reproduced from (Liu et al, 2015) with permission. b Bright field image of an enucleated porcine eye and isolated cornea proper following chemical application.…”
Section: Abbreviationsmentioning
confidence: 99%